Analisis Kebutuhan Pengembangan Bahan Pembelajaran Biologi Sel STKIP YPM Bangko - Eko Wulandari (Jurnal Biotek, 2023)
This research was conducted to evaluate the importance of developing teaching materials in cell biology that can support the learning process and improve students' comprehension to achieve the learning objectives. The study employed a descriptive qualitative approach using survey methods. Questionnaires and observation sheets were utilized as research instruments. To collect data, the observation sheets were provided to students attending cell biology lectures, while the questionnaires were distributed to students who had completed cell biology courses in the biology education study program at STKIP YPM Bangko. Descriptive analysis techniques were applied to analyze the data obtained from the student questionnaires and ongoing lecture process observation sheets. The findings of this research underscore the significance of creating well-designed and engaging teaching materials in the form of modules for cell biology. These materials aim to enhance students' understanding and foster an active, creative, and critical learning.